Prostaglandin F2α Induces Goat Corpus Luteum Regression via Endoplasmic Reticulum Stress and Autophagy - Wen, Xin; Liu, Lu; Li, Shanshan; Lin, Pengfei; Chen, Huatao; Zhou, Dong; Tang, Keqiong; Wang, Aihua; Jin, Yaping (Frontiers in Physiology, 2020)
Corpus luteum (CL) is a transient endocrine tissue that produces progesterone for maintaining pregnancy in mammals. In addition, the regression of CL is necessary for the initiation of the estrous cycle. Extensive research has shown that the prostaglandin F2α (PGF2α) induces the regression of CL in ruminants. However, the mechanisms of endoplasmic reticulum (ER) stress and autophagy in the regression of goat CL induced by PGF2α are still unclear. In this study, ovaries of dioestrus goats and goats that were 3 months pregnant were collected to detect the location of the ER stress-related protein GRP78. The relationship between the different stages of the luteal phase of goat CL during estrous cycle and changes in the expression of ER stress-related proteins and autophagy-related proteins was confirmed by western blot analysis. The results showed that both ER stress and autophagy were activated in the late luteal phase of the goat CL. To reveal the function of ER stress and autophagy in the CL regression process induced by PGF2α, we used 4-phenyl butyric acid (4-PBA) and chloroquine (CQ) for inhibiting ER stress and autophagy, respectively. Through the apoptotic rate detected by the ﬂow cytometry and the expression of ER stress- and autophagy-related proteins detected by western blotting, we demonstrated that ER stress promoted goat luteal cell apoptosis and autophagy, and that apoptosis can be enhanced by the inhibition of autophagy. In addition, knockdown of EIF2S1, which blocked the PERK pathway activation promoted apoptosis by reducing autophagy in goat luteal cells treated with PGF2α. In conclusion, our study indicates that ER stress promotes goat luteal cell apoptosis to regulate the regression of CL and activates autophagy to inhibit the goat luteal cell apoptosis via PERK signaling pathway.